(untitled) (Comprehensive Journal of Science, 2025)
In the experiment 200 unsexed one-day-old broiler chicks were used, 100 chicks from (Cobb) strain and 100 from (Ross) strain. The chicks were reared in a closed house located on the western mountain region, Libya. during the period from July 13, to 24 August 2024. The house was divided into 10 replicates, 5 replicates per strain, and 20 birds per replicate. Chicks were fed a starter diet 22% protein for the first three weeks, followed by a grower-finisher diet 20% protein until seventh week of age. in the end of week seven, five birds from each replicate were weighed before and after slaughter to evaluate the productive traits and calculate dressing percentage.The average values of body weight, feed intake, weight gain, feed conversion ratio, and mortality rate were recorded weekly. live body weight and carcass weight were measured after slaughter and removal of feathers and internal organs.The results revealed a significant effect of strain (P≤0.05) on body weight, where Cobb strain showed a superiority over the Ross. No significant differences were observed in feed intake, except for the third and fourth weeks. results showed a significant effect (P≤ 0.05) of strain on weekly weight gain started from week 3 to week 6, where Cobb exhibiting higher gains than Ross. However, no significant strain effect (P≤0.05) on feed conversion ratio, except in the first week. Regarding mortality, significant effect was observed only during the first, second, and sixth weeks, Furthermore, significant differences (P≤0.05) between strains were recorded in live body weight and carcass weight.